REVIEW ON PARAMETER OPTIMIZATION OF SELF LUBRICATING BEARING - Rohitkumar Gangarde; R. R. Kharde; Avinash Jagtap (International Journal of Innovations in Engineering Research and Technology, 2021)
The Self Lubricating Bearing is used in Electronic Motors, Fuel Pumps, Actuators, Household Appliances etc. Self Lubricating Bearings are manufactured only by Powder Metallurgy, since Porosity needed for Oil Content can be achieved only by Powder Metallurgy. High Oil Content is desired for better operation of bearing. Oil Content depends on parameters like Powder Weight, Density of Component, Sintering Temperature and Sintering Speed etc. The Bearing manufactured by GKN Sinter Metals has Weight around 22-25 gm andDensity around 5.8-6.0 gm/cc with Oil content about 18-20%. The main objective of the project is to optimize the parameter values to achieve